Analisis Pemanfaatan Konten Video Tiktok sebagai Media Pembentukan Karakter di Era Masa Kini - Abdullah, Khadijah Razali; Yusrianti, Susi; Daud, Al Husaini M.; Fauzan, Fauzan (Pase: Journal of Contemporary Islamic Education, 2023)
The rapid advancement of digital technology has significantly transformed patterns of communication and information consumption in society, including in the realm of character education. TikTok, as one of the most popular social media platforms today, serves not only as a source of entertainment but also holds potential as a medium for learning and character development. This study employs a library research approach with descriptive analysis. Data was collected through a comprehensive review of relevant literature on character education, social media, and TikTok content creators. Additionally, observations were conducted on TikTok videos containing educational and Islamic values, along with an analysis of media consumption patterns across different user groups. The findings reveal that TikTok content presents two contrasting dimensions: entertainment-oriented content that may lead to moral degradation, and educational content that can foster positive character traits. Adult users tend to be more autonomous in filtering content, whereas children and adolescents require intensive supervision. The role of parents and educators is crucial in guiding content consumption to ensure a positive impact on students’ character development. TikTok can be effectively utilized as a character-building medium when its use is directed wisely and accompanied by appropriate supervision. Collaboration among users, educators, and parents is essential to maximize TikTok’s educational potential.